Mirror meetings with frail older people and multidisciplinary primary care teams: Process and impact analysis - Sietske Grol; Gerard Molleman; Henk Schers (Wiley, 2019)
Abstract Objectives To analyse the process and impact of confronting multidisciplinary teams (MTs) in primary care with the experiences of frail older patients through mirror meetings (MMs), with the aim of supporting teams to organize care in a more patient‐oriented way. Methods Process and impact analyses were performed using a mixed‐method approach. MMs were held with 14 frail older patients and four MTs comprising 23 health‐care professionals (HCPs) in primary care in the Netherlands. Results Mirror meetings were feasible for frail older people living at home, although their recruitment was time‐consuming. Interaction between the patients was scarce, but they valued the opportunity to share their stories. HCPs preferred MMs overwritten reports about patient experiences. An impact analysis revealed four dominant professional areas for improvement: improve alignment with patient goals, improved communication with patients both orally and in writing, developing new pathways to connect with informal caregivers and an increased understanding that most HCPs are relative strangers to their patients. Conclusions Mirror meetings are a relatively simple and promising method for exploring the ways in which frail older patients experience care. Practice implications Given the right conditions, MMs could result in valuable processes to enable MTs to improve their working methods.